Uma proposta metodológica para o ensino dos números complexos: história e prática. - Queiroz, Paulo Alexandre Sousa (2016)
Given the low learning outcomes presented by large-scale assessments of indicators such as: SPAECE and PISA, one sees the challenging environment for math education in Brazilian public schools, especially in didactic transposition of content deemed abstract and the methodology used for execution teaching. Given this reality, this paper presents an educational proposal of complex numbers, structured from the Fedathi sequence as a methodology through hand-in-pocket pedagogy. Research hi directed to thirty-five students of third year of a public school in vocational education of Ceara. The goal was to provide a methodological possibility to professor of mathematics in the teaching of all complex numbers, mainly because it is a content difficult to practice visualization. three teaching sessions were applied using the four steps proposed in Fedathi sequence: making position, maturity, and solution testing. an analysis from the results obtained in the pre-test to compare the qualitative and quantitative results of the post-test as well as a profile analysis of the subjects involved in the research will be done. Finally, it is expected that the Sequence Fedathi methodology, used as a methodological resource, promotes the teacher in mediating the teaching of complex numbers.